Model-Driven Engineering and Software Development : 4th International Conference, MODELSWARD 2016, Rome, Italy, February 19-21, 2016, Revised selected papers /: 4th International Conference, MODELSWARD 2016, Rome, Italy, February 19-21, 2016, Revised selected papers. (2017) - Unknown
No abstract available